Comparative Study of Serum Electrolytes in Diabetic and Non-Diabetic People of Different Age and Gender from Basrah Province, Iraq: Studi Perbandingan Elektrolit Serum pada Penderita Diabetes dan Non-Diabetes dengan Usia dan Jenis Kelamin yang Berbeda dari Provinsi Basrah, Irak - Hassan, Saged S.; Salman, Nader A.; Hussein, Shahla A. (Indonesian Journal on Health Science and Medicine, 2024)
The present study aimed at investigating differences in the levels of the most important blood electrolytes in diabetic patients of different age and gender and compare it with levels recorded in normal control group from Basrah Province. The theoretical hypothesis of the research relay on the possible impact of hyperglycemia caused by this disease on the osmotic status and electrolyte distribution between extra- and intracellular fluids. Blood samples were collected from 50 diabetic patients ranging in age from 27 to 62 years and are registered in the Diabetes Department of Al-Faiha’a Educational Hospital in Basrah and compared with 50 control group of nearly same ages. The sample include both males and females. Results of the present investigation revealed significant differences in electrolyte levels between diabetic and non-diabetic groups. Both Na+ and Cl- showed a significant decrease in diabetes patients suggesting the occurrence of hyponatrmia and hypochloromia cases respectively. On contrary K+ ion showed a significant elevation in diabetes patients compared with control which reflects hyperkalemia cases. No significant changes were noticed in the case of serum Ca++ and phosphorus. Results were discussed in view of the findings of other studies on the osmotic status of diabetic patients Highlights: Analyzed electrolyte differences in diabetic vs. non-diabetic individuals. Compared Na+, Cl-, K+, Ca++, and phosphorus levels in 100 participants. Significant hyponatremia, hypochloremia, and hyperkalemia found in diabetic patients. Keywords: Serum Electrolytes, Diabetes, Age, Gender , Basrah.